OC-055 Ibd Passport-developing An Evidence-based Internet Travel Resource For Inflammatory Bowel Disease: A Report Of The Initial Stages Of Implementation. (9th June 2014) - Greveson, K; Shepherd, TC; Hamilton, MI; Murray, C
Abstract : Introduction: Travellers with Inflammatory bowel disease (IBD) are at greater risk of travel-related morbidity [1], with ECCO recommending expert consultation prior to travel, particularly for those on immunosuppression .2 The travel consult and patients pre-travel preparation have been found to be deficient .1 Here we present the development of a dedicated IBD travel advice website to enable informed, safe travel with IBD. Methods: We conducted a literature review using Ovid databases and a search of existing online material using major internet search engines to identify existing research and resources regarding IBD and travel. Data was extracted from a recently reported prospective survey 3 of 136 IBD patients which examined pre-travel preparation and experiences of travelling with IBD. Results: The database and Internet search revealed a paucity of research and resources available for IBD patients and professionals regarding travel and IBD. Our survey of 136 patients found 60% [82/136] reported IBD affected travel, however; pre-travel medical advice was only sought by 24% [32/136]. Disease-related travel knowledge was poor with 52% of immunosuppressed patients unaware of the need to avoid live vaccines; only 53/136 (39%) buy travel insurance covering their IBD and the majority of these (70%) pay a premium. 91% (124/136) would find a dedicated IBD travel website useful. As a result of this, IBDPassport™ was developed for both patients and professionals as non-commercial, IBD-specific travel resource, aimed at providing evidence-based information on all aspects of travel and IBD. The functionality of the website includes an interactive map of country specific advice including vaccinations and a 'search and refer' service for IBD professionals to refer to other IBD centres globally. Features also include practical information for travelling with IBD and specific information for the immunocompromised traveller. Conclusion: We present the first comprehensive web-based travel resource created for both IBD patients and professionals to obtain evidence-based IBD and country specific travel information. IBDPassport™ needs to be formally evaluated by patients and healthcare professionals as part of a larger study and to inform further development. References: 1 Rahir et al . ECCO 2009 2 Soonawala et al . Inflamm Bowel Dis 2012 3 Greveson et al . A Recent Flare of Disease does not Prohibit Travel: Early Results of a Single Centre Study in Inflammatory Bowel Disease and Travel. Abstract Number: A-1908. ECCO 9 th congress Copenhagen 2014 Disclosure of Interest: None Declared.